THE EFFECT OF BREASTFEEDING TECHNIQUE EDUCATION VIA BOOKLET MEDIA ON BREASTFEEDING BEHAVIOR AMONG MOTHERS WITH INFANTS AGED 0-6 MONTHS - shofia ageng pertiwi (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
The low coverage of exclusive breastfeeding in Tuban Regency, ranging from 45% to 50%, presents a critical public health issue largely attributed to insufficient maternal knowledge of correct breastfeeding techniques. This study aimed to analyze the effect of breastfeeding technique education using booklet media on the breastfeeding behavior of mothers with infants aged 06 months at Puskesmas Plumpang, Tuban Regency. A quantitative study with a quasi-experimental, one-group pretest-posttest design was conducted, involving 32 mothers recruited via total sampling. Data were gathered through questionnaires and analyzed using the Wilcoxon Signed Rank Test. Results indicated that prior to the intervention, 59.4% of mothers exhibited adequate behavior and 40.6% exhibited poor behavior, with no participants demonstrating good behavior. Following the intervention, 90.6% of mothers demonstrated good behavior and 9.4% showed adequate behavior. Statistical analysis yielded a Z-value of -5.160 (p < 0.001), confirming a significant positive effect of the intervention. Booklet media is an effective tool for improving breastfeeding practices. Continuous education from pregnancy through the postpartum period is recommended to enhance maternal knowledge and skills, thereby supporting the success of exclusive breastfeeding.